Education hubs and private higher education expansion in small island developing states contexts: The case of Mauritius - Hyleen Mariaye; Michael Samuel (Transformation in Higher Education, 2018)
Background: This article is located in the context of governments of small island developing states supporting education hubs in collaboration with local and global partners. Whilst current literature on the development of education hubs focuses on the macro policy perspectives looking at how education hub policies are designed and enacted upon at national level, there are relatively few studies on the micro perspective of the institutions.